Randomized Trial of Cisplatin versus Firocoxib versus Cisplatin/Firocoxib in Dogs with Transitional Cell Carcinoma of the Urinary Bladder. (3rd December 2012) - Knapp, D.W.; Henry, C.J.; Widmer, W.R.; Tan, K.M.; Moore, G.E.; Ramos‐Vara, J.A.; Lucroy, M.D.; Greenberg, C.B.; Greene, S.N.; Abbo, A.H.; Hanson, P.D.; Alva, R.; et al.
<x xml:space="preserve">Abstract</x> Background Cisplatin combined with a nonselective cyclooxygenase (cox) inhibitor has potent antitumor activity against transitional cell carcinoma (TCC) in dogs, but this treatment is limited by renal toxicosis. Cox‐2 is expressed in TCC, but only in limited sites within the kidney. A cox‐2 inhibitor could enhance the antitumor activity of cisplatin with potentially fewer adverse effects on the kidney. Hypothesis Cisplatin/cox‐2 inhibitor treatment will have greater antitumor activity but no more renal toxicosis than cisplatin alone in dogs with TCC. Animals Forty‐four dogs with naturally occurring urinary bladder TCC. Methods Dogs were randomized to receive cisplatin (60 mg/m2 IV q21d), firocoxib (5 mg/kg PO q24h), or the combination. Tumor measurements were determined before and at 6‐week intervals during treatment. Renal function was monitored by serum creatinine concentration, iohexol clearance, and urine specific gravity. Toxicoses were graded according to Veterinary Co‐Operative Oncology Group (VCOG) criteria. Results The remission rate with cisplatin/firocoxib (57%) was significantly (P = .021) higher than that with cisplatin alone (13%). Renal and gastrointestinal toxicoses were common in dogs receiving cisplatin, but there were no significant differences between dogs receiving cisplatin or cisplatin/firocoxib. Firocoxib alone induced partial remission or stable disease in 20 and 33% of dogs, respectively. Conclusions Firocoxib significantly enhanced the antitumor activity of cisplatin resulting in partial remission in more than half of the cases. The toxicoses inherent to cisplatin, however, were noted in dogs receiving this combination. Firocoxib had antitumor effects as a single agent and can be considered a palliative treatment for dogs with TCC.